Designing and the Pilot Trial of Bivalve Molluscan Fishing Quotas on Maoming Coastal Waters of China, Northern South China Sea - Lyu, Shaoliang; Deng, Siman; Lin, Kun; Zeng, Jiawei; Wang, Xuefeng (Frontiers in Marine Science, 2022)
In the context of the declining fishery resources, some active management measures have been taken to strive for the sustainable development of fisheries. However, these input-oriented control management measures have not been realized the expectation in alleviating the depressing depletion of fishery resources. The fishing quotas (FQ) system, an output-oriented control management method, has been proved to be effective in curbing overfishing and conserving fishery resources. But it has not been formally implemented in China until now. Thus, it is urgent to start the pilot trial on the implementation of the FQ system in China. We firstly formulated a framework for the FQ system on bivalve fisheries, and then conducted an empirical analysis based on the field survey of bivalve mollusks in Maoming shallow waters, Guangdong, northern South China Sea. The species composition, dominant species, and density distribution of bivalves were analyzed. The swept-area method was used to assess the total allowable catch (TAC) of bivalves. Each step of the FQ system was discussed in depth. Results showed that a total of 45 bivalve species were identified. Meretrix planisulcata and Ruditapes philippinarum were the two dominant species. The spatial distribution of density varied largely. The estimated TAC value is 4.28×105 kg that can be allocated to fishermen under the regulations of FQ system. Finally, the framework for FQ system was improved in every step of the future procedure, including target species selection, TAC determination, quotas allocation, catch report, and fishing supervision. The general framework of FQ system in this study can also be referenced to other economically important fish or other marine organisms.